Phase II study of neratinib in older adults with HER2 amplified or HER2/3 mutated metastatic breast cancer. Issue 5 (June 2021) - Yuan, Yuan; Lee, Jin Sun; Yost, Susan E.; Stiller, Tracey; Blanchard, M. Suzette; Padam, Simran; Katheria, Vani; Kim, Heeyoung; Sun, Canlan; Tang, Aileen; Martinez, Norma; Patel, Niki Dipesh; et al.
Abstract: Objective: The tolerability and efficacy of targeted therapy in older adults with cancer has not been adequately studied. Neratinib is a novel HER1, HER2, HER4 tyrosine kinase inhibitor that has recently been granted FDA approval for treatment of breast cancer. The major toxicity of neratinib is diarrhea, which affects up to 90% of patients. This phase II trial evaluates the safety and tolerability of neratinib in adults ≥60. Methods: Patients aged 60 or older with histologically proven metastatic breast cancer and HER2 amplification (defined by ASCO/CAP guideline) or HER2/HER3 activating mutation were enrolled to receive neratinib at 240 mg daily in 28-day cycles. The association between tolerability, defined as dose reduction and number of completed courses, and log2 Cancer and Aging Research Group (CARG) toxicity risk score was assessed using a Student's t -test and linear regression, respectively. Response rate, progression free survival, and overall survival were also evaluated. Results: 25 patients were enrolled with median age of 66 (range 60–79). Seventy-six percent of patients were white, 16% Asian, and 8% African-American. Seventy-six percent were patients with hormone receptor (HR) positive metastatic breast cancer (MBC) and 24% were patients with HR negative MBC. Median number of prior lines of metastatic therapy were 3 (range 0–11). 20/25 (80%) had worst grade toxicities ≥2. A total of 9/25 (36%) had grade 3 toxicities including 5/20 (20%) diarrhea, 2/20 (8%) vomiting, and 2/20 (8%) abdominal pain. There were no grade 4 or 5 toxicities. A total of 9/25 (36%) had dose reduction, and 2/25 (8%) discontinued therapy due to toxicity. The association between dose reductions and CARG toxicity score reached borderline statistical significance suggesting a trend with participants with higher CARG toxicity risk scores being more likely to require a dose modification ( p = 0.054). 1/25 (4%) had a partial response, 11/25 (44%) had stable disease, 12/25 (48%) had progression of disease, and 1/25 (4%) was not assessed. Median progression free survival (PFS) was 2.6 months (95% CI [2.56–5.26]), and median overall survival (OS) was 17.4 months (95% CI [10.3, NA]). Conclusions: Neratinib was safe in this population of older adults with HER2 amplified or HER2/3 mutated metastatic breast cancer (BC). Higher CARG toxicity risk score may be associated with greater need for dose adjustments. Future studies are needed to confirm this finding.